Odpowiedzi

Najlepsza Odpowiedź!
2010-03-08T10:11:50+01:00
Najpierw trzeba wyliczyć współczynnik a,
a) A (5,-10) ; B (0,5)
a=[yB-yA]/[xB-xA]
a=[5+10]/[0-5]=15/5=3
a=3
równanie kierunkowej prostej
y-yA=a(x-xA)
y+10=3(x-5)
y+10=3x-15
y=3x-15-10
y=3x-25-wzór

b) A (0,0) ; B (6,10)
a=[10-0]/[6-0]=10/6=1i2/3
a=1i2/3
y-0=5/3(x-0)
y-0=5/3x-0
y=5/3x-wzór

c) A (3,-2) ; B (6,0)
a=[0-2]/[6-3]=-2/3
a=-2/3
y+2=-2/3(x-3)
y+2=-2/3x+2
y=-2/3x+2-2
y=-2/3-wzór

d) A (-4,1) ; B (0,9)
a=[9-1]/[0+4]=8/4=2
a=2
y-1=2(x+4)
y-1=2x+8
y=2x+8+1
y=2x+9-wzór

e) A (-6,8) ; B ( -3,0)
a=[0-8]/[-3+6]=-8/3
a=-2i2/3
y-8=-8/3(x+6)
y-8=-8/3x-16
y=-8/3x-16+8
y=-8/3x-8-wzór

f) A (0,6) ; B (-4,0)
a=[0-6]/[-4-0]=-6/4=-1i1/2
a=-1i1/2
y-6=-3/2(x-0)
y-6=-3/2x
y=-3/2x+6-wzór
15 4 15